2021
DOI: 10.22456/1679-9216.102600
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between PD-L1 Expression and Tumor-Infiltrating Lymphocytes in Canine Mammary Tumor

Abstract: Background: Studies pointed out that the tumor-infiltrating lymphocytes (TILs) have considerable importance in canine mammary tumor (CMT). On the other hand, cancer cells sometimes find ways to use immune checkpoint proteins as a shield to avoid being identified and attacked by the immune system as programmed death 1 ligand 1 (PD-L1). In this study, it was investigated the relationship between PD-L1 expression, stromal tumor-infiltrating lymphocytes (TILs) in canine mammary tumor (CMT), and the association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…2,23 In our study, PD-L1 expression was positively correlated with CK5/6 expression and was not utilized from a PD-L1 study in human breast cancer, applying the criteria to dogs may require modification due to interspecies differences. To overcome these limitations, we modified the evaluation method to consider cases as PD-L1 positive when at least 1% of the tumor cells were immunolabeled, according to the study by Lopes-Neto et al 20 We selected a polyclonal antibody used by Ariyarathna et al, 3 which showed a correlation between PD-L1 IHC expression and the histopathological grade of CMCs. The lack of correlation between PD-L1 IHC expression and histopathological grade in this study, in contrast to a previous study that used the same antibody, may be attributed to the different evaluation methods employed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,23 In our study, PD-L1 expression was positively correlated with CK5/6 expression and was not utilized from a PD-L1 study in human breast cancer, applying the criteria to dogs may require modification due to interspecies differences. To overcome these limitations, we modified the evaluation method to consider cases as PD-L1 positive when at least 1% of the tumor cells were immunolabeled, according to the study by Lopes-Neto et al 20 We selected a polyclonal antibody used by Ariyarathna et al, 3 which showed a correlation between PD-L1 IHC expression and the histopathological grade of CMCs. The lack of correlation between PD-L1 IHC expression and histopathological grade in this study, in contrast to a previous study that used the same antibody, may be attributed to the different evaluation methods employed.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have employed diverse evaluation methods, including varying scales for labeling intensity and cutoff values for determining PD-L1 positivity. 3,20 In previous studies on CMCs, Ariyarathna et al 3 quantified PD-L1 IHC expression by considering the labeling intensity using a scale ranging from 0 to 3, and Lopes-Neto et al 20 evaluated PD-L1 IHC positive or negative cells when 1% of the tumor cells showed labeling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results in CMTs are scarce and contradict those of BC. In one study, CMTs with low TILs a had significantly higher OS than neoplasm with high TILs count [ 48 ], while in another study tumours with intratumoural low TILs count also had significantly higher OS, while peripheral TILs count did not have an association with OS [ 49 ]. The cause for the difference in BC and CMTs results could be the much bigger sample sizes in studies done with BC with a better analyzation of the results by meta-analysis.…”
Section: Discussionmentioning
confidence: 99%